Prediksi Peningkatan Kebutuhan Tenaga Listrik Provinsi Jambi Tahun 2020-2025 - Tri Isra Janwardi (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2020)
Nowaday, electricity is the main energy to our daily activity. Increasment of population amount became one of factor that effect to increase the electricity consumption. Increased need of electricity consumtion is need to analized to guarantee the electricity needs that support the economic growth. Analized of electricity needs can be analized from some sector, those are: household sector, industrial sector, business sector, and social sector. Electricity consumption in each sector is depend on income, amount of costumer, and the price of electricity that applied by PT PLN by each of sector. The research is descriptive form in econometrics analize at Jambi Province. The result of the analized by SPSS and excel, the increasment of electricity consumption, those are: household sector (23,89%), industrial sector (21,03%), business (18,29%), and social sector (7,06%) from 2020 till 2025 at Jambi Province